My younger sister's age today is 3 times what it will be 3 years from now minus 3 times what her age was 3 years ago. Find her present age.
Let the present age of my younger sister be x years.
Then, her age after 3 years = (x + 3) years
Also, her age 3 years ago = (x - 3) years
It is given that her present age is 3 times her age after 3 years minus 3 times her age 3 years ago.
Therefore, we obtain the following equation
x = 3(x + 3) - 3(x - 3)
⇒x=3x+9−3x+9 [using the distributive property]⇒x=18 years
Hence, her present age is 18 years.